Hierarchical control of parallel voltage source inverters in AC microgrids. Issue 16 (21st January 2019) - Li, Zhongwen; Cheng, Zhiping; Xu, Yali; Wang, Yifan; Liang, Jing; Gao, Jinfeng
Abstract : Here, a distributed hierarchical control strategy is proposed for the parallel operating of voltage source inverters (VSIs) in AC microgrids (MGs). For the output voltage control of a VSI, conventional double‐loop proportional‐integral (PI) control method has deteriorative performance under disturbance parameters conditions and has a narrow range of stable operation. Here, the sliding mode control (SMC)‐based inner‐loop current control (level0) and mixed H 2 / H ∞ ‐based outer‐loop voltage control (level1) are proposed for the output voltage control of a VSI, which combines the advantages of robustness and fast transient response. The droop control (level2) is applied to avoid circulating currents among the VSIs without using any critical communication between them. The multi‐agent system (MAS)‐based distributed economic automatic generation control (EAGC) and distributed automatic voltage control (AVC) (level3) are proposed to restore the voltage magnitude and frequency deviations caused by droop controller and achieve optimal active power dispatch at the same time.